1980
DOI: 10.1126/science.6892734
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocarcinogenicity of Glandless Cottonseeds and Cottonseed Oil to Rainbow Trout ( Salmo gairdnerii )

Abstract: Glandless cottonseed kernels are available for purchase and consumption by the general public. These kernels contain no gossypol but still have a full complement of naturally occurring cyclopropenoid fatty acids, which in rainbow trout are active as synergists with aflatoxins and primary liver carcinogens. Diets containing glandless cottonseed kernels or a lightly processes cottonseed oil produced significant numbers of hepatocellular carcinomas in rainbow trout after 1 year. The much greater incidence of canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0
1

Year Published

1985
1985
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(38 citation statements)
references
References 19 publications
1
36
0
1
Order By: Relevance
“…O resultado do estudo dos ácidos graxos da Sterculia striata reforça o relatado na literatura sobre a presença de compostos com grupos ciclopropênicos em óleos de sementes de plantas da família Sterculiaceae 6,7 . Desta forma, não se recomenda a ingestão das amên-doas de chichá e o óleo só será próprio para fins comestíveis se tais ácidos forem eliminados 4,9,24 . …”
Section: Resultsunclassified
“…O resultado do estudo dos ácidos graxos da Sterculia striata reforça o relatado na literatura sobre a presença de compostos com grupos ciclopropênicos em óleos de sementes de plantas da família Sterculiaceae 6,7 . Desta forma, não se recomenda a ingestão das amên-doas de chichá e o óleo só será próprio para fins comestíveis se tais ácidos forem eliminados 4,9,24 . …”
Section: Resultsunclassified
“…Namely, Hendricks et al [6] failed to prove the presence of tumors on 144 necropsies in brown bullheads (Ictalurus nebulosus), but tumor incidence in the same type of fish taken from polluted waters ranged 30% on the sample of 532 [6] . Neoplasms do appear in all non-mammalian vertebrates and this is important in and of itself since these animals can serve as models to understand the behaviour and trajectory of such tumors in mammals and humans.…”
Section: Comparative Oncologymentioning
confidence: 99%
“…Dietary CFAs caused lesions, increased glycogen deposition, and elevated saturated fatty acid concentration in the liver in rainbow trout (Struthers et al 1975a, b). The CFAs are powerful carcinogens when fed in combination with aflatoxins for rainbow trout (Hendricks et al 1980) and sockeye salmon (Wales and Sinnhuber 1972). These compounds also induced hepatomas without aflatoxins in rainbow trout (Hendricks et al 1980).…”
Section: Cyclopropenoic Fatty Acidsmentioning
confidence: 99%
“…The CFAs are powerful carcinogens when fed in combination with aflatoxins for rainbow trout (Hendricks et al 1980) and sockeye salmon (Wales and Sinnhuber 1972). These compounds also induced hepatomas without aflatoxins in rainbow trout (Hendricks et al 1980). Dietary CFAs alter the activity of several liver enzymes (Eisele et al 1983), including the inhibition of fatty acid desaturases (Roehm et al 1970) which may explain the accumulation of saturated fatty acids found in the liver of fish fed CFAs.…”
Section: Cyclopropenoic Fatty Acidsmentioning
confidence: 99%